Programa de Atendimento Residencial: Sharing knowledge in care management with professionals in the Health Care Network of Cascavel/PR (Research, Society and Development, 2022)
Objective: To understand the conformation of Programa de Atendimento Residencial (PAR), as well as the profile of patients cared for by PHC professionals, in the municipality of Cascavel/PR. Methodology: This is a field research, with a bibliographic, descriptive, retrospective and documentary character with a quantitative approach. Data were collected from the electronic medical record, for the period from June 2018 to June 2021 and distributed in tables. Results: The study sample consists of 379 patients, of wich 53,3% (n= 202) are male. Regarding the age group, 41,2% (n= 156) are between 60 and 79 years old. About the underlying pathologies, cardiovascular and/or metabolic diseases stood out, representing 38,3% (n= 145). As for mobility, 46,2% are bedridden, wich may contribute to a high incidence of pressure injuries, being represented by 33,8% (n= 128). Another revealing data is that 37% (n= 140) of 379 patients have one or more devices, wich requires shared and multidisciplinar care. Conclusion: Despite its weakness, PAR presentes itself as an educative and training componente, providing matrix and technical-pedagogical support to professionals, mainly for the PHC, contributing to their empowerment, in addition to being a servisse model with the possibility of replication in other counties.